KETERKAITAN FAKTOR BIOFISIK DAN PENGUASAAN LAHAN HUTAN DENGAN KERAWANAN KEBAKARAN HUTAN DALAM PERSPEKTIF PENATAAN RUANG : STUDI KASUS PADA WILAYAH HTI DI JAMBI - Andri Yushar Andria; Baba Barus; Fredian Tonny Nasdian (Jurnal Ilmu Tanah dan Lingkungan, 2010)
The occurrence of forest fire in Jambi can be considered as an annual phenomenon. It happenes almost every year in every type of land uses, including industrial timber plantation area of PT Wirakarya Sakti. The drivers of fire are a combination between natural factors and an anthropogenic factor, which in this case is traditional land preparation activity conducted by local farmer. To maintain their source of livelihoods, farmers convert forest land into seasonal agricultural land (ladang) using ‘slash and burn’ method. This activity occures along with the changes in social economic condition. Currently, although this circumstance has existed for a long time, availability of information regarding forest fire-prone area especially in industrial timber plantation is really minutes. Based on this condition, this study aims to model and develop spatial information on the vulnerability forest fire in industrial timber plantation (HTI) area. The specific objectives are: 1) To identify biophysical factors that affect of forest fire, 2) To identify the significance of community activities and land tenure factors to forest fires event in the area, 3) To analyze communities motivations and actions in regards to forest fire events, and 4) To analyze synergy between actual land use with HTI Spatial Planning (RTR-HTI). The results of using logistic regression analysis showed that the most significance biophysical variable are soil type and rainfall, while on the anthropogenic variable are the distance from land and the distancefrom road. Pearson correlation analysis and regression analysis suggested that community motivations and actions are affected by social indicators. Based on these facts, spatial analysis using GIS was conducted. The result showed that the value of land use suitable (LUS) was 88.1% (218,289 ha) and not suitable was 11.9% (29,589 ha) from the land allocation of RTR-HTI. Using Analytic Hierarchy Process (AHP), the relative importance weight for each factor was derivied to be included in hazard model. The hazard map showed that fire hazard can be classified into high category (118,925 ha), moderate category (175,272ha) and low category (11,369 ha). Keywords: land use, land tenure community, vulnerability forest fire